Evaluation of the Impacts of ASEAN+3 FTAs on Vietnam Iron and Steel Trade Flows: Gravity Model Analysis - Thu, Nguyễn Anh; Hiên, Đỗ Thị Mai (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 30 No 5E, 2014)
Abstract: This paper analyzes the impacts of ASEAN+3 FTAs onVietnam iron and steel trade flows. In this respect, a gravity model is applied to the panel data covering 27 top trading partners of Vietnam from 2001 to 2012. The paper findings show positive impact of ACFTA and VJEPA on increasing imports of iron and steel into Vietnam while AKFTA, AFTA and VJEPA have positive effects on their export. AJCEP and AFTA are concluded to have little impact on either imports or exports. Keywords: Vietnam, ASEAN+3, steel, gravity model.